2016
DOI: 10.3390/rs8080653
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Lidar Estimation of Aboveground Forest Biomass in the Absence of Field Inventory

Abstract: Abstract:The scientific community involved in the UN-REDD program is still reporting large uncertainties about the amount and spatial variability of CO 2 stored in forests. The main limitation has been the lack of field samplings over space and time needed to calibrate and convert remote sensing measurements into aboveground biomass (AGB). As an alternative to costly field inventories, we examine the reliability of state-of-the-art lidar methods to provide direct retrieval of many forest metrics that are commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 38 publications
3
31
0
1
Order By: Relevance
“…For field-measured trees, the average CBH was 7.63 m with a standard deviation of 4.51 m, the average tree height was 23.97 m with a standard deviation of 9.31 m and the average DBH was 44.22 cm with a standard deviation of 21.38 cm. For LiDAR-derived trees, the average crown diameter was 8.98 m with a standard deviation of 3.14 m; the average tree height was 22.35 m with a standard deviation of 9.29 m. The average height of LiDAR-derived trees was 1.62 m (6.76%) lower than that of field-measured trees, which indicated that LiDAR-derived tree height was slightly lower than the field-measured ones likely for two reasons: 1) it is often difficult for LiDAR laser beam to hit the exact tops of trees [51], and 2) it is often difficult to measure tree height accurately in the field [54]. Table 2 shows the summary of the field measurements for matched trees.…”
Section: Field Measurement Results and Tree-to-tree Matchingmentioning
confidence: 93%
“…For field-measured trees, the average CBH was 7.63 m with a standard deviation of 4.51 m, the average tree height was 23.97 m with a standard deviation of 9.31 m and the average DBH was 44.22 cm with a standard deviation of 21.38 cm. For LiDAR-derived trees, the average crown diameter was 8.98 m with a standard deviation of 3.14 m; the average tree height was 22.35 m with a standard deviation of 9.29 m. The average height of LiDAR-derived trees was 1.62 m (6.76%) lower than that of field-measured trees, which indicated that LiDAR-derived tree height was slightly lower than the field-measured ones likely for two reasons: 1) it is often difficult for LiDAR laser beam to hit the exact tops of trees [51], and 2) it is often difficult to measure tree height accurately in the field [54]. Table 2 shows the summary of the field measurements for matched trees.…”
Section: Field Measurement Results and Tree-to-tree Matchingmentioning
confidence: 93%
“…Figure 7a,b provide a perspective view of a single acquisition dataset and the high-density point cloud calculated by merging the registered individual acquisitions, respectively. The latter represents the forest structure at a finer resolution in both horizontal and vertical dimensions and enables the lidar forest inventory at the individual tree level, which is crucial for the monitoring of tree mortality as well as for tree biomass estimates over areas with non-existent field sampling [20,21]. Furthermore, the merging of multiple acquisitions improves mapping of the surface vegetation characteristics that highly impact the wildfire hazard and behavior [37,38].…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, high density point clouds (>8 pt/m 2 ) allow direct extraction of forest metrics alleviating the need for costly and time-consuming field work [20,21], reduce uncertainty in forest metrics estimation (e.g., maximum and mean height of canopy) [22], and better represent understory and near-surface vegetation [23]. Therefore, we have the opportunity to markedly improve the forest structure characterization by coherently fusing the weekly ASO measurements (~1 pt/m 2 ) in order to significantly increase the point density (up to~12 pt/m 2 ) and provide a multi-year dataset that is then optimal for any type of lidar-based assessment of vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…From a LiDAR point cloud, certain forest parameters can be determined, such as: aboveground forest biomass [7][8][9], Leaf Area Index (LAI) [10][11][12][13][14] or canopy density [15,16]. Furthermore, LiDAR covered by dense forest vegetation).…”
Section: Introductionmentioning
confidence: 99%